Giovanni Gozzer and the reform of secondary schools in Italy during the Seventies - Gaudio, Angelo (Rivista di Storia dell’Educazione, 2021)
This article deals with the role played by Giovanni Gozzer in opposition to the secondary school reform in Italy during the second half of the Seventies. Drawing on the arguments of the international debate, which he knew in great detail, he defended the ongoing middle school reforms of 1962 but opposed the proposals for the secondary school reforms, considering them to be promoted principally by the communist party which even seemed to succeed in holding sway over the left-wing reformist Christian democrats.